MEDIATISASI RUPA KOTA DALAM IKLAN MEIKARTA: Spectacle, Hiperealitas dan Simulakra - Anwar, Khairil (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2018)
The advertisment of Meikarta, aired on the television was a promotion from property sales by Lippo Group. This paper describes the process of comodification in view editing by doing a binary oposition between Jakarta which was imaged by inferior and superior Meikarta. On the narrative, this advertisement shows hippereality and simulacra in delivering the advertisment content. Objectification also was done to make consumers interest of being a part of Meikarta which is not only buy the use value but also sign value. So as to enable unconsciously the consumers show spectacle effort when they become a part of the imajinary city. To cite this article (7th APA style): Anwar, K. (2018). Mediatisasi Rupa Kota dalam Iklan Meikarta: Spectacle, Hiperealitas dan Simulakra [The Mediatization of a City in the Meikarta Ad]. Journal Communication Spectrum, 8(2), 147-165. http://dx.doi.org/10.36782/jcs.v8i2.1852